2022
DOI: 10.3390/su142214789
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cloud Computing Implementation Drivers for Sustainable Construction Projects—A Structural Equation Modeling Approach

Abstract: Sustainability aspects should be adopted during all the decision-making stages of executing construction projects to gain maximum benefits without compromising the objective of such projects. Cloud computing has been a valuable tool for sustainable construction success in several countries over the last two decades. Cloud computing and its drivers have undoubtedly improved the sustainable success target of cost, quality, and time. However, cloud computing implementation in Nigeria’s construction industry is mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…CMB is especially problematic when information is gained through self-administered questionnaires , survey-based approach and cross-sectional variables (AL-Khatib & Ramayah, 2023). To rule out CMB, Harman's one-factor test was conducted in SPSS (Kineber et al, 2022), the results demonstrated that the first indicator accounts for 38.43% of the overall variance which is less than 50% hence CMB is not influencing the outcome of this study .…”
Section: Common Methods Bias (Cmb)mentioning
confidence: 87%
“…CMB is especially problematic when information is gained through self-administered questionnaires , survey-based approach and cross-sectional variables (AL-Khatib & Ramayah, 2023). To rule out CMB, Harman's one-factor test was conducted in SPSS (Kineber et al, 2022), the results demonstrated that the first indicator accounts for 38.43% of the overall variance which is less than 50% hence CMB is not influencing the outcome of this study .…”
Section: Common Methods Bias (Cmb)mentioning
confidence: 87%
“…Fargnoli et al [64]'s study established suitable techniques for preventing and managing risks that can be applied as intelligent agents for the implementation of the OHSs required by the construction industry. Kineber et al [65] attempted an integral analysis of OHSMSs with respect to implementation based on OHSAS 18001. A lack of commitment and knowledge concerning safety was a significant challenge hindering the implementation of OHSMSs in the building industry.…”
Section: Ohsms Implementationmentioning
confidence: 99%
“…Respondents judged the benefits of cyber technology based on their knowledge and experience using a 5-point Likert scale, with 5 being extremely high, 4 being high, 3 being average, 2 being small, and 1 denoting no or a very small. This scale was used in some previous studies [57][58][59][60][61][62][63][64]. In this study, convenience sampling approaches were used.…”
Section: Data Collection and Case Studymentioning
confidence: 99%